Resilience and socialization between public servers: a case study at the Federal University of Mato Grosso - UFMT (Research, Society and Development, 2019)
The aim with this work examining the relationship between resilience and organizational socialization among public servants of a University Publishes. The research on organizational socialization indicate that the adaptation of the individual to a new position and a new organisation tends to be a stressful event. Resilience, which describes the processes of overcoming stress and adversity, could aid understanding of the differences in the results of socialization among individuals in the same organization. Based on this assumption, the sample selection criterion of research was the social group of technical-administrative servers in education inducted from the year 2012 at the Federal University of Mato Grosso UFMT. Crossbreeding analysis of data and information have been developed in order to observe and compare the predictive ability of resilience in relation to organizational socialization. The results showed, in General, that negative aspects regarding the process of socialization, especially on items and proactivity, not integration organization and professional qualification, have shown that servers do not understand and don't realize the effectiveness of this process. However, despite the difficulties and even if it's not institutional socialization is occurring in some way, especially in their individual sectors. The practical implications, limitations and main contributions of the study are discussed, with suggestions for future research, as well as comparing the predictive capacity of resilience in relation to organizational socialization among the new servers in the institution of higher education.